(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Tiktashatpal Ghrita is a classical polyherbal Ayurvedic formulation traditionally used in the management of various types of Kustha (skin disorders). The present study focuses on the pharmacognostical identification of its constituent ingredients and the physico-chemical evaluation of the formulation. Macroscopic and powder microscopy of the raw drugs confirmed the authenticity and quality of the ingredients used. Organoleptic assessment of the coarse powder prepared from crude drugs met the prescribed standards. The formulation was further analyzed for key physico-chemical parameters: the acid value was found to be 4.2815, the saponification value 0.227, refractive index 1.4710 (at room temperature), specific gravity 0.9071 (at room temperature), and loss on drying 1.6177%. High-Performance Thin Layer Chromatography (HPTLC) analysis was performed using an optimized solvent system, which revealed a maximum of five distinct spots. The similarity of Rf values in the alcoholic extract indicated the presence of certain consistent phytoconstituents across batches. All analytical procedures were carried out in accordance with standard protocols, contributing to the quality assessment and standardization of Tiktashatpal Ghrita.